Self-assembled quinoxaline derivative: Insight into disaggregation induced selective detection of nitro-aromatics in aqueous medium and live cell imaging. (December 2021) - Basak, Megha; Bhattacharjee, Basu; Ramesh, Aiyagari; Das, Gopal
Abstract: Advancement in fluorescent chemosensor for discriminative and precise detection of picric acid (PA) in aqueous medium is highly desirable owing to its alarming impact on the natural environment via soil and groundwater pollution. To this end, we have successfully fabricated a quinoxaline-based receptor (Probe 1 ) to detect PA in 100% aqueous medium. Probe 1 self-assembled to form leaf-like structures in pure water as micro aggregates (∼940 nm) and transformed entirely into smaller spherical shape (∼354 nm) upon addition of PA. DFT analysis and lifetime experiment validated that both PET and FRET from the electron-rich Probe 1 to electron-deficient PA are concurrently responsible for effective fluorescence quenching. The self-assembled probe exhibited excellent selectivity towards PA (Ksv of 22.6 × 10 6  M −1 ) with a ∼56 ppb detection limit. Importantly, PA detection on solution-coated paper strips was achieved at the picogram level. Furthermore, to evaluate the practical usefulness, the probe has been used to detect PA in actual water and soil samples. Interestingly, Probe 1 was non-toxic to cultured HeLa cells and rendered detection of intracellular picric acid through live cell imaging. Graphical abstract: Quinoxaline derived fluorescent chemosensor unveils noteworthy selectivity and sensitivity towards picric acid amidst all NACs in aqueous medium along with morphological transformation from leaf-like assembly to smaller spherical shaped structures. Image 1 Highlights: Quinoxaline based receptor prone to self-assemble to leaf-like structures. Sensitive and selective "Turn-off" detection of PA (LOD = ∼56 ppb) in aqueous medium. Disassembly tendency (smaller spherical shape) of self-aggregated probe towards PA. Paper based detection achieved at pictogram level. Determination of PA in real water samples, soil samples and in vivo cellular system.